Incidence of metabolic syndrome and determinants of its progression in Southern Iran: A 5-year longitudinal follow-up study - Bakhshayeshkaram, Marzieh (J Res Med Sci, 2020)
BACKGROUND: Metabolic syndrome (MetS) is a cluster of conditions increasing the risk of serious diseases. This study aimed to define the predictors of MetS incident in a community-based cohort in Southern Iran, during a mean follow-up period of 5.1 years. MATERIALS AND METHODS: During the mean follow-up period of 5.1 years, a cohort study was conducted on 819 Iranian adults aged ≥18 years at baseline and followed to determine the incidence and predictors of MetS progression in Shiraz, a main urban region in the southern part of Iran. The International Diabetes Federation Guideline was used to detect the MetS. Multiple Cox's proportional hazards models were also used to estimate the predictors of new-onset MetS. RESULTS: The prevalence of MetS was 25.9% at baseline, and the overall incidence of subsequent MetS was 5.45% (95% confidence interval [CI]: 4.47–6.59). The incidence of MetS was significantly higher in women (7.12% [95% CI: 5.52–9.05]) than in men (3.92% [95% CI: 2.80–5.34]). Moreover, it increased by 5.02 (95% CI, 3.75–6.58) among individuals who had one metabolic component and by 12.65 (95% CI, 9.72–16.18) for those who had three or more components (P < 0001). The incidence of MetS was also analyzed using the multiple Cox's proportional hazards model for potential risk factors, and it was revealed that female gender (hazard ratio [HR] 2.45; 95% CI: 1.33, 4.50; P = 0.004), higher body mass index (HR 3.13; 95% CI: 1.43.6.84; P = 0.012), increased abdominal obesity (HR 1.45; 95% CI 0.85, 2.46; P = 0.045), smoking (HR 4.79; 95% CI 2.09, 10.97; P < 0.001), and lower high-density lipoprotein (HR 0.53; 95% CI: 0.29, 1.00; P = 0.044) significantly predicted the onset of MetS at baseline; however, age, systolic and diastolic blood pressure, serum uric acid, fasting blood glucose, cholesterol, triglyceride and creatinine, estimated glomerular filtration rate, marital status, level of education, and level of physical activity did not independently predict the onset of MetS when other covariates were considered. CONCLUSION: This study showed the high-incidence rates of MetS in males and females residing in Southern Iran. Therefore, the prevention through community-based lifestyle modification should be implemented to reduce the burden of MetS and its complications.